Virtual Machine Placement using Interactive Artificial Bee Colony Algorithm(VMPIABC) - Kumar, Shubham; Tripathi, Atul (International Journal of Computer Sciences and Engineering, 2021)
As cloud computing is becoming part of our life day by day, it has attracted research community to tackle the research problems of cloud computing environment. Virtual machine placement is a brewing area for cloud researchers so in the proposed model virtual machine placement problem is modelled as an optimization problem with the objective of resource wastage. As huge resource wastage can affect the cloud service provider so, an virtual machine placement algorithm based on interactive artificial bee colony was proposed. The performance of the proposed method is thoroughly compared with other competing algorithms through exhaustive experiments and results are presented.